The use of value chain analysis of information in determining the most important the accounting information - ابراهيم, لبنى زيد; كاظم, اشواق طالب (Journal of Economics and Administrative Sciences, 2014)
The use  analysis  value chain such  information in the provision as financial  so information quality meet and satisfy the needs of users such information , particularly investors and lenders   as the identification needs   financial information and the knowledge as their behavior influenced by that information can be based on the accounting profession to focus on improving their function in order to achieve its goal that satisfying their needs and rationalize their decisions . In accounting thought discovered fertile ground for users preferences as one of the entrances   theorising positive which is based on the need to include knowledge on accounting hypothesis that explain the behavior   users as accounting information to reflect the information shown in the financial statements of their preferences and then fit their use of current and futuristic  through interpretation and prediction of their behavior , which is one of the essential  activities  in value   information has been the use in which information determining  characteristics  and convenience of representation sincere more important for As is the quality of accounting information  the grade benefit  if they were employed   information in the best possible way for the benefit of the users of information dissimilar not only to their forms decision but also in terms of their behavior and style of their awareness depending on the way of thinking and reflexes and response to cognitive-based culture, accounting, administrative, and the time period  financial statements because the more realize and understand user information whenever they are more suitable for decision adds to know where his